First 3‐D simulations of meteor plasma dynamics and turbulence - Oppenheim, Meers M. (2015)
Millions of small but detectable meteors hit the Earth's atmosphere every second, creating trails of hot plasma that turbulently diffuse into the background atmosphere. For over 60 years, radars have detected meteor plasmas and used these signals to infer characteristics of the meteoroid population and upper atmosphere, but, despite the importance of meteor radar measurements, the complex processes by which these plasmas evolve have never been thoroughly explained or modeled. In this paper, we present the first fully 3‐D simulations of meteor evolution, showing meteor plasmas developing instabilities, becoming turbulent, and inhomogeneously diffusing into the background ionosphere. These instabilities explain the characteristics and strength of many radar observations, in particular the high‐resolution nonspecular echoes made by large radars. The simulations reveal how meteors create strong electric fields that dig out deep plasma channels along the Earth's magnetic fields. They also allow researchers to explore the impacts of the intense winds and wind shears, commonly found at these altitudes, on meteor plasma evolution. This study will allow the development of more sophisticated models of meteor radar signals, enabling the extraction of detailed information about the properties of meteoroid particles and the atmosphere.